Preference of negatively charged membranes in magnesium and lithium separation by nanofiltration - Lulu Liu; Shihong Lin; Xinyi Xu; Yinhua Wan; Weijie Song; Jianquan Luo (Nature Communications)
Abstract Despite the traditional co-ion competition theory suggesting that positively charged nanofiltration (NF) membranes are best for Li⁺/Mg²⁺ separation, practical applications predominantly utilize negatively charged membranes. Furthermore, most biological ion channels in nature are characterized by negatively charged functional groups. To address this theoretical discrepancy, we conducted a comprehensive study that integrates experimental data with molecular dynamics simulations to explore the transport behavior of Mg²⁺ and Li⁺ through negatively charged NF membranes. When using mixed salt solutions as feed, NF membranes with strong negative charges and small pore sizes achieved a high rejection of Mg²⁺ (>90%), with a Li⁺ rejection as low as −53.2%. This remarkable selectivity is primarily driven by the proposed ion competition mechanism termed counter-ion competition. For weakly hydrated monovalent counter-ions, such as Li⁺, the enrichment of strongly hydrated counter-ions like Mg²⁺ near the membrane pores facilitates the dehydration of Li⁺ at the pore entrance, thereby reducing its size exclusion effect. Simultaneously, this dehydration enhances the electrostatic interaction between Li⁺ and the negatively charged NF membrane, resulting in high permeability of Li⁺. Our work advances the understanding of ion-selective transport in NF membranes, offering mechanistic guidance for developing high-performance NF membranes for Li⁺/Mg²⁺ separation.